2017
DOI: 10.1111/jgh.13895
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease Clinical

Abstract: Introduction: Recent evidence has indicated that an accelerated infliximab dosing regimen may reduce early colectomy rates in patients with acute severe ulcerative colitis (ASUC). However, there are limited data on rates of mucosal healing in those who receive accelerated regimens compared with standard dosing. Achieving mucosal healing has been unequivocally associated with better clinical outcomes. Aim: To determine whether accelerated infliximab induction achieves higher rates of endoscopic mucosal healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…After the removal of duplicates, 594 records remained, 565 of which were excluded by titles and abstracts. The remaining 29 articles were assessed for eligibility by full-text and further 10 studies were excluded due to the following reasons: three studies reported only short-term follow-up data (39-41), one study did not report on the timing and rate of colectomy (38) and two studies were uncontrolled (42,43). In two studies, the number of patients treated with CYS and IFX was not reported (44,45), one study included patients pre-treated with either CYS or IFX (46) and one study evaluated patients with Crohn's colitis (47).…”
Section: Search Resultsmentioning
confidence: 99%
“…After the removal of duplicates, 594 records remained, 565 of which were excluded by titles and abstracts. The remaining 29 articles were assessed for eligibility by full-text and further 10 studies were excluded due to the following reasons: three studies reported only short-term follow-up data (39-41), one study did not report on the timing and rate of colectomy (38) and two studies were uncontrolled (42,43). In two studies, the number of patients treated with CYS and IFX was not reported (44,45), one study included patients pre-treated with either CYS or IFX (46) and one study evaluated patients with Crohn's colitis (47).…”
Section: Search Resultsmentioning
confidence: 99%